A numerical comparison of the flow behaviour in Friction Stir Welding (FSW) using unworn and worn tool geometries - Hasan, Ahmed; Bennett, Chris; Shipway, P.H. (Elsevier, 2015)
The tool is a key component in the Friction Stir Welding (FSW) process, but the tool degrades and changes shape during use; however, only a limited number of experimental studies have been undertaken in order to understand the effect that worn tool geometry has on the material flow and resultant weld quality. In this study, a validated model of the FSW process is generated using the CFD software FLUENT, with this model then being used to assess the detail of the differences in the flow behaviour, mechanically affected zone (MAZ) size and strain rate distribution around the tool for both unworn and worn tool geometries. Comparisons are made at two different tool rotational speeds using a single weld traverse speed. The study shows that there are significant differences in the flow behaviour around and under the tool when the tool is worn. This modelling approach can therefore be used to improve understanding of the effective limits of tool life for welding, with a specific outcome of being able to predict and interpret the behaviour when using specific weld parameters and component geometry without the need for experimental trials.